Implementation Of Improving Tour Guide Skills In Gastronomic Tourism In Bandung City - Rusmiati, Debi; Turgarini, Dewi; Ningsih, Caria (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Gastronomy of cities in the world initiated by UNWTO criteria since 2004 aims to promote cooperation between cities around the world. The capital of a city in making its city a gastronomic tourism trend is not only to have potential but in terms of packaging must also be considered. Tourists who visit with the aim of tasting are incomplete if not accompanied by information related to the philosophy and history contained. It is necessary to intervene from a tour guide who provides information so that tourists have a new experience. The ability of the tour guide not only provides information related to the place but also needs interpretation and knowledge of philosophy, ethics and culture. This study seeks to answer these problems by describing the skills of gastronomic tour guides. This research uses the Analytical Hierarchy Process (AHP) method by interviewing 26 panelists in the city of Bandung. The results of AHP data processing show that the criteria for on-site management expertise have the highest weight to be owned by gastronomic tour guides in the city of Bandung. Furthermore, the alternatives that have the highest weight are looking for unique experiences, in-depth information related to regional gastronomic tourism, general information about gastronomic activities, and gastronomic knowledge and expertise and managing activities in a structured manner. Based on the results obtained, the skills of gastronomic tour guides are different from other tour guides. Special guidelines for gastronomic tour guides are needed so that it is hoped that Bandung City will further improve the quality of gastronomic tourism services in the city of Bandung to become a culinary city for tourists and can become one of the cities that are in demand by gastronomic tourists. This research can be a recommendation for gastronomic tour guides to pay attention to the skill aspects of gastronomic tour guides.